2019
DOI: 10.1111/zph.12631
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of enteric non‐typhoidal Salmonella in humans in the Middle East and North Africa: A systematic review and meta‐analysis

Abstract: To enhance efforts related to controlling foodborne pathogens in the Middle East and North Africa (MENA), information on epidemiology of non‐typhoidal Salmonella enterica (hereafter termed “Salmonella”) is limited. We quantified the overall regional and country‐specific Salmonella prevalence in different human populations and identified the most common serotypes. Published literature of Salmonella prevalence was systematically reviewed and reported following the Preferred Items for Systematic Reviews and Meta‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
3
16
1
Order By: Relevance
“…The rate of salmonellosis incidence varies between countries across the Arab World and is influenced largely by the absence of systematic, harmonized national and regional surveillance and reporting systems. According to a recent systematic review and meta-analysis on prevalence of enteric NTS in humans in the Arab world, the highest pooled Salmonella prevalence measures were in Morocco (17.9%, 95% CI: 5.7-34.8%, 1997-2012), Tunisia (10.2%, 95% CI: 4.3-18.0%, 1988-2009) and Sudan (9.2%, 95% CI: 6.5-12.2%, 2006-2008), while the lowest were in Jordan (1.1%, 95% CI: 0.1-3.0%, 1993-2010), Oman (1.2%, 95% CI: 1.2%-1.3%, 1998-2002) and Palestine (1.2%, 95% CI: 0.4-2.1%, 1999-2011) [15]. Several published studies indicate that the most widely reported serovars associated with acute diarrheal disease across the Middle East are the Salmonella serovars typhimurium and enteritidis [71][72][73].…”
Section: Non-typhoidal Salmonella In the Food Chain In The Arab Worldmentioning
confidence: 94%
See 2 more Smart Citations
“…The rate of salmonellosis incidence varies between countries across the Arab World and is influenced largely by the absence of systematic, harmonized national and regional surveillance and reporting systems. According to a recent systematic review and meta-analysis on prevalence of enteric NTS in humans in the Arab world, the highest pooled Salmonella prevalence measures were in Morocco (17.9%, 95% CI: 5.7-34.8%, 1997-2012), Tunisia (10.2%, 95% CI: 4.3-18.0%, 1988-2009) and Sudan (9.2%, 95% CI: 6.5-12.2%, 2006-2008), while the lowest were in Jordan (1.1%, 95% CI: 0.1-3.0%, 1993-2010), Oman (1.2%, 95% CI: 1.2%-1.3%, 1998-2002) and Palestine (1.2%, 95% CI: 0.4-2.1%, 1999-2011) [15]. Several published studies indicate that the most widely reported serovars associated with acute diarrheal disease across the Middle East are the Salmonella serovars typhimurium and enteritidis [71][72][73].…”
Section: Non-typhoidal Salmonella In the Food Chain In The Arab Worldmentioning
confidence: 94%
“…Measuring the prevalence of NTS in food products is important to quantify the risk of foodborne Salmonella infections in humans in the Arab World. According to a recent metaanalysis study by Rifai et al [15], the pooled prevalence of NTS in the human population in the Arab countries was estimated at 6.6% (95% confidence interval (CI): 5.4-7.9%). In 2019 [15], Rifai et al conducted a systematic review and meta-analysis to summarize current data on national and regional specific NTS prevalence in foods in the MENA region.…”
Section: Non-typhoidal Salmonella In the Food Chain In The Arab Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the survival and multiplication of salmonellosis in the environment and in food is influenced by temperature (Milazzo et al 2016 ). In the EMME region, non-typhoidal Salmonella cases were reported in Lebanon, Saudi Arabia, Bahrain, Iraq, and Kuwait (Al-Rifai et al 2019 ). Although the knowledge on campylobacteriosis in the Middle East is limited, Campylobacter species are a major and increasing cause of gastroenteritis in this region (Kaakoush et al 2015 ).…”
Section: Current Impacts Of Climate Change On Infectious Diseases In the Emmementioning
confidence: 99%
“…Humans, on the other hand, can become infected by coming into contact with live animals or being in an environment contaminated with animal feces and then accidently ingesting pathogens [ 8 , 19 ]. The systematic reviews and meta-analyses: a step-by-step guide will be used to quantify and summarize the findings of these studies [ 20 ]. Few systematic reviews and meta-analyses studies have been performed in sub-Saharan Africa and Africa in the last ten years on invasive nontyphoidal Salmonella (iNTS) disease and the prevalence of Salmonella [ 8 , 21 23 ].…”
Section: Introductionmentioning
confidence: 99%